Estimating groundwater recharge for an arid karst system using a combined approach of time‐lapse camera monitoring and water balance modelling. Issue 5 (20th September 2015) - Schulz, Stephan; de Rooij, Gerrit H.; Michelsen, Nils; Rausch, Randolf; Siebert, Christian; Schüth, Christoph; Al‐Saud, Mohammed; Merz, Ralf
Abstract: Groundwater is the principal water resource in semi‐arid and arid environments. Therefore, quantitative estimates of its replenishment rate are important for managing groundwater systems. In dry regions, karst outcrops often show enhanced recharge rates compared with other surface and sub‐surface conditions. Areas with exposed karst features like sinkholes or open shafts allow point recharge, even from single rainfall events. Using the example of the As Sulb plateau in Saudi Arabia, this study introduces a cost‐effective and robust method for recharge monitoring and modelling in karst outcrops. The measurement of discharge of a representative small catchment (4.0 · 10 4  m 2 ) into a sinkhole, and hence the direct recharge into the aquifer, was carried out with a time‐lapse camera. During the monitoring period of two rainy seasons (autumn 2012 to spring 2014), four recharge events were recorded. Afterwards, recharge data as well as proxy data about the drying of the sediment cover are used to set up a conceptual water balance model. The model was run for 17 years (1971 to 1986 and 2012 to 2014). Simulation results show highly variable seasonal recharge–precipitation ratios between 0 and 0.27. In addition to the amount of seasonal precipitation, this ratio is influenced by the interannual distribution of rainfall events. Overall, an average annual groundwater recharge for the doline (sinkhole) catchment on As Sulb plateau of 5.1 mm has estimated for the simulation period. Copyright © 2015 John Wiley & Sons, Ltd.